2017
DOI: 10.6061/clinics/2017(08)01
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to BCLC recommendations for the treatment of hepatocellular carcinoma: impact on survival according to stage

Abstract: OBJECTIVES:This study sought to assess the adherence of newly diagnosed hepatocellular carcinoma patients to the Barcelona Clinic Liver Cancer system treatment guidelines and to examine the impact of adherence on the survival of patients in different stages of the disease.METHODS:This study included all patients referred for the treatment of hepatocellular carcinoma between 2010 and 2012. Patients (n=364) were classified according to the Barcelona Clinic Liver Cancer guidelines. Deviations from the recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
0
19
1
2
Order By: Relevance
“…To consider the risk of liver failure and tumor burden in the terminal stage of HCC, DAA was not prescribed in our general practice; therefore, this stage was excluded. A previous study revealed that the OS in stage D patients was worse in patients adherent to HCC therapy than in nonadherent patients [29]. AASLD guidance recommends that patients with a life expectancy of less than 12 months are unlikely to benefit from HCV eradication and therefore palliative care is suggested [30].…”
Section: Plos Onementioning
confidence: 99%
“…To consider the risk of liver failure and tumor burden in the terminal stage of HCC, DAA was not prescribed in our general practice; therefore, this stage was excluded. A previous study revealed that the OS in stage D patients was worse in patients adherent to HCC therapy than in nonadherent patients [29]. AASLD guidance recommends that patients with a life expectancy of less than 12 months are unlikely to benefit from HCV eradication and therefore palliative care is suggested [30].…”
Section: Plos Onementioning
confidence: 99%
“…In this regard, the Barcelona Clinic Liver Cancer (BCLC) classification accomplishes these goals (105) . This system has been extensively used worldwide (106) and in Brazil (1,107) . Importantly, several other classifications are mentioned in American, European, and Asian literature such as TNM, Cancer of the Liver Italian Program (CLIP), Hong Kong Liver Cancer (HKCL), and Japanese Integrated Staging (JIS) score (108)(109)(110)(111) .…”
Section: Staging and Classification For Treatment Allocation: A New Lmentioning
confidence: 99%
“…To determine the prognostic value of Twist for HCC patients, univariate and multivariate analyses were performed on the clinicopathological characteristics and Twist expression levels of patients (Table II). Univariate analysis revealed that OPN expression, Twist expression, serum AFP level, hepatitis B surface antigen, tumor size, tumor capsulation, vascular invasion, Barcelona Clinic Liver Cancer stage (41) and tumor differentiation were significantly associated with the OS and TTR times of patients with HCC (Table II). However, no prognostic significance for OS or TTR was observed in association with the other characteristics, including sex, age, liver cirrhosis, ALT and tumor number.…”
Section: Univariate and Multivariate Analyses Of The Prognostic Valuementioning
confidence: 99%